1988
DOI: 10.1007/bf02550607
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous renal cyst aspiration and treatment with alcohol

Abstract: Twenty-two simple renal cysts of 16 patients were aspirated under guidance of ultrasound, with a 20-gauge needle with stylet. Sixteen of those cysts were treated with 96% alcohol. All cysts that were not treated with alcohol recurred within 10 weeks. Treatment with alcohol revealed no recurrences in 3 months follow-up for 12 patients and 6 months follow-up for 4 patients. No major complications were encountered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…The possible role of coagulative necrosis after percutaneous ethanol injection therapy has been investigated in a variety of diseases. Percutaneous ethanol injection therapy is currently a steadily growing therapeutic method that is widely used in the ablation of solid and cystic masses (hyperparathyroidism, hepatic cysts and carcinomas [7, 8]). Local infiltration of pure ethanol has been demonstrated to lead to cell death by causing cell membrane lysis, protein denaturation and vascular occlusion resulting in a coagulative necrosis of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of coagulative necrosis after percutaneous ethanol injection therapy has been investigated in a variety of diseases. Percutaneous ethanol injection therapy is currently a steadily growing therapeutic method that is widely used in the ablation of solid and cystic masses (hyperparathyroidism, hepatic cysts and carcinomas [7, 8]). Local infiltration of pure ethanol has been demonstrated to lead to cell death by causing cell membrane lysis, protein denaturation and vascular occlusion resulting in a coagulative necrosis of tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In aspiration alone, the destruction of epithelial cell lining will not happen and the epithelial cells will continue secreting fluid cyst. In other words the cyst fluid re-accumulates (4). Secretory epithelial lining the cyst wall must be destructed in order to prevent recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, destruction of cysts occur without affecting the renal parenchyma. Ethanol as a sclerosing agent has been mentioned in the literature, and there are studies that have reported success rates of over 90% (1, 2, 4). Akinci and colleagues treated 98 simple renal cysts with percutaneous ethanol sclerotherapy with a single session technique (2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations